FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN NELAYAN TANGKAP DI DESA BONGO KECAMATAN BATUDAA PANTAI KABUPATEN GORONTALO - Indara, Sofyan R; Bempah, Irwan; Boekoesoe, Yuriko (AGRINESIA : Jurnal Ilmiah Agribisnis, 2017)
This study aims: 1) to determine the effect of factors on the income of fishermen in the Village Bongo Batudaa District Beach. 2) to analyze how the income of fishermen in Bongo Village, Batudaa Pantai District. The research method used in this research is survey with data analysis using descriptive analysis and multiple linear analaisis. The results of this study show: 1) Capital, labor, experience and mileage to sea together have real effect on the income of fishermen in Bongo Village, Batudaa Pantai District. While partially only capital and mileage of the sea that influences very real, while the labor and experience have no effect. 2) The average income of fisherman respondents in Bongo Village, Batudaa Pantai District is Rp. 7,473,852 every three months.